GIS based mapping of spatio-temporal distribution pattern of ribbonfish Trichiurus lepturus (Linnaeus, 1758) along Saurashtra coast, India - Abdul Azeez, P.; Mohammed Koya, K.; Mathew, K. L.; Temkar, G. S.; Khileri, R. A. (Indian Journal of Fisheries, 2016)
Identification of spatio-temporal distribution of fish species represents fundamental information for stock assessment which in turn is essential for formulation of fishery management plans as well as for GIS based decision making. This study investigated the spatio-temporal distribution and abundance of different life stages of ribbonfish, Trichiurus lepturus (Linnaeus, 1758) off Saurashtra coast. Geographical coordinates of fishing and allied information on the time of fishing, depth of the fishing area as well as catch details were collected using a structured schedule, from selected trawlers operated from Veraval. Information was mapped using a GIS software to get the spatio-temporal distribution of the species. It was observed that juveniles were more abundant along the south Saurashtra coast whereas subadults and adults showed a discontinuous distribution with abundance in the waters off south Saurashtra as well as north Saurashtra coasts.